PANDANGAN HUKUM ISLAM TERHADAP LARANGAN PERKAWINAN PADA TRADISI PELA GANDONG (Studi Kasus Di Desa Ohilahin Kabupaten Buru Maluku) - Yuni Arti Nurlatun; Masrokhin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study was motivated by the prohibition of marriage in the Pela Gandong tradition between the Nurlatun and Lesnusa clans in Ohilahin Village, Buru Regency, Maluku. This tradition is based on an oath of brotherhood inherited from ancestors and is considered sacred, so that violations of it are believed to bring disaster. This study aims to understand the causes of the prohibition, the implementation of customary law against violators, and examine the views of Islamic law on the prohibition. The study used a qualitative method with a normative-empirical approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that: (1) the prohibition of marriage is based on an oath of peace due to the history of conflict between clans; (2) violations of the Pela Gandong tradition are resolved through customary deliberation and the imposition of social sanctions; and (3) Islamic law in principle does not prohibit inter-clan marriage if there is no mahram relationship, but respects local cultural values that are in line with the principles of brotherhood and social harmony.